Therapeutic effects of Citrullus colocynthis fruit in patients with type II diabetes: A clinical trial study - Batol Barghamdi; Fereshteh Ghorat; Khairollah Asadollahi; Kourosh Sayehmiri; Robab Peyghambari; Ghobad Abangah (Wolters Kluwer Medknow Publications, 2016)
Aim: Citrullus colocynthis plant was traditionally used for the treatment of diabetes in Sabzevar city, Iran. This study aimed to investigate the effects of C. colocythis on fasting blood sugar (FBS) and HbA1c in patients with type II diabetes. Materials and Methods: Totally 70 patients with type II diabetes attending the diabetes clinic in Sabzevar city were investigated. Patients were divided into two groups of intervention and placebo randomly and were studied for 2 months. Mean serum level of FBS and HbA1c was compared within and between groups at the end of the study. Data were analyzed using student and paired t-tests via SPSS software version 16. Results: A significant difference was revealed between before and after intervention for HbA1c and FBS levels in the intervention group (P = 0.01 and P = 0.04, respectively). The difference between before and after intervention for FBS and HbA1c levels in the placebo group were not significant (P = 0.8, P = 0.68 respectively). This study showed a negative relationship between either the mean ± standard deviation serum level of FBS or HbA1c and body mass index in the treatment group significantly (P = 0.03, 0.008, respectively). The present study did not identify any side effects during the study period among the treatment group. Conclusion: According to the findings of this study, application of 125 mg C. colocynthis once per day for 2 months can lead to considerable decrease in the mean levels of HbA1c and FBS among the patients with type II diabetes without any side effects.